Calculating organ and effective doses in paediatric interventional cardiac radiology based on DICOM structured reports – Is detailed examination data critical to dose estimates?. (January 2019) - Karambatsakidou, Angeliki; Omar, Artur; Fransson, Annette; Poludniowski, Gavin
Highlights: Doses calculated using data from radiation dose structured reports (RDSR) No differences in average dose, estimated with RDSR- or a simplified method. Conversion coefficients presented for organ doses in paediatric heart catheterization. Abstract: Purpose: To estimate effective dose (E), equivalent organ doses (HT ) and associated conversion coefficients (CCE:KAP = E/KAP, CCHT:KAP = HT /KAP; KAP = Kerma-area product) in paediatric cardiac interventions, using detailed exposure data from radiation dose structured reports (RDSR). These "RDSR dose estimations" have been compared with estimations performed using the approach currently implemented in the clinic that is based on a simplified assumptions method (SAM). Methods: The Monte Carlo system PCXMC, incorporated into a previously developed framework, was used to calculate E and HT for 202 children. The calculations were performed with input values from RDSR, and also using simplified assumptions, including fixed nominal values for the focus-skin distance, collimated beam size, irradiation geometry and patient size (age, weight and height). Results: Mean HT to critical organs were: 5–25 mSv (lungs), 5–8 mSv (breasts) and 5–22 mSv (heart), with the lower and upper end of the doses associated with the neonatal and 15 years group, respectively. The associated mean CCHT:KAP for the different age groups were: 9.4–1.6 mSv/Gycm 2 (lungs), 8.9–0.54 mSv/Gycm 2 (breasts) and 9.3–1.4 mSv/Gycm 2 (heart). Conclusions: The extension of the concept of a conversion coefficient for HT is introduced and CCHT:KAP values for paediatric cardiac interventions divided in age groups are presented. This method of linking the KAP to HT is intended for use in epidemiological/cohort studies or in clinics that do not have access to RDSR. Further, the population-averaged conversion coefficients for the critical organs estimated from RDSR, displayed no statistically significant difference compared with the SAM approach.